Dierstoker - Lim, Darryl Yan Kai (2017)
Dierstoker is a top down based game about a boy’s (Mori) journey to find his father, and his transition into adulthood. Set in a mountainous forest, Dierstoker is a combination of an adventure and a survival game that tests a player’s ability to plan attacks while managing his available resources and methods of survival. Dierstoker's narrative plays out using visual cues over text or speech, which adds an additional layer to the overall gameplay mechanics, testing the player’s wit and creativity to solve puzzles to the next step in the game.